Grit. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2023)
"In the face of hardship, you need motivation and determination. You need grit. But how do you build it? This book explores how you can persist in even the most trying of situations. With a mix of psychological research, expert advice, and real-life examples, you'll learn how to convince yourself to do hard things, deal with overwhelming feelings and stay calm in the moment, and identify when needing too much grit means it's time to quit"--
To Build Grit, Go Back to Basics : recognize your story and know your core purpose / an interview with Shannon Huffman Polson by Curt Nickisch -- Gauging Your Grit : a personal assessment / Thomas H. Lee and Angela L. Duckworth -- How to Deal with High Pressure Situations at Work : aim for emotional stability / by Tomas Chamorro-Premuzic -- How to Convince Yourself to Do Hard Things : learn to embrace discomfort / by David Rock -- "Mentors Were What Helped Me Survive" : to build strength, don't go it alone / an interview with Misty Copeland by Alison Beard -- When to Grit, and When to Quit : beware the dark side of determination / by André Spicer -- Are you Pushing Yourself Too Hard? : taking care of yourself is essential to long-term success / by Rebecca Zucker -- How to Cultivate Gratitude, Compassion, and Pride :they're the best way to instill grit and grace on your team / by David DeSteno -- Organizational Grit : turn passion and perseverance into performance / by Thomas H. Lee and Angela L. Duckworth.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 14, 2023).
WorldCat record variable field(s) change: 050
Keywords: Determination (Personality trait); Employee motivation; Job stress; Perseverance (Ethics); Success in business; Détermination (Trait de personnalité); Personnel -- Motivation; Persévérance (Morale); Succès dans les affaires; Determination (Personality trait); Employee motivation; Job stress; Perseverance (Ethics); Success in business; elektronické knihy; electronic books